Response to In Vitro Micropropagation of Plants with Different Degrees of Variegation of the Commercial Gymnocalycium cv. Fancy (Cactaceae) - Carles Cortés-Olmos; Vladimir Marín Guerra-Sandoval; Carla Guijarro-Real; Benito Pineda; Ana Fita; Adrián Rodríguez-Burruezo (Plants)
This study aims to establish efficient in vitro propagation protocols for Gymnocalycium cv. Fancy, an ornamental cactus with variegated variants, by evaluating the effects of cytokinin type and explant source on the organogenic response. Plants with different degrees of variegation (0–100%) were classified by size to obtain different explant types (apices, central discs, epicotyls, and hypocotyls). The effects of 6-Benzylaminopurine (BAP, 8 µM), Kinetin (KIN, 4 µM), and Thidiazuron (TDZ, 1 µM) were assessed on shoot production, callus formation, and rhizogenesis. Additionally, we studied the relationship between initial plant variegation and the productivity of the variegated shoots. The best shoot production results were obtained for central discs treated with 1 µM TDZ. Furthermore, a correlation was observed between the activated areole type (green, mixed, or fully colored) and shoot color percentage, enabling precise explant selection. The appearance of differently colored shoots confirms the potential for selecting new lines from this cultivar too. These findings hold significant potential not only for the breeding and propagation of ornamental cacti but also for the cultivation of other edible cacti and their relatives.